MANAJEMEN ERA OTONOMI DAERAH: PEMERINTAH DAERAH SEBAGAI VALUE CREATING SYSTEM - Eko Walujo Suwardyono (Journal of Management and Business, 2002)
Since local autonomy regulation have been implemented efectively in one year, but empirically it still has many euphoria coming from institution process and Local Government management. Weak commitment and unclear strategic implementation of Local Government for value creating system cause poor quality of good governance and public accountability. This article presents an idea for a paradigm of Local Government strategic role through value creating system.